2021
DOI: 10.1186/s12974-021-02184-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting S100A4 with niclosamide attenuates inflammatory and profibrotic pathways in models of amyotrophic lateral sclerosis

Abstract: Background An increasing number of studies evidences that amyotrophic lateral sclerosis (ALS) is characterized by extensive alterations in different cell types and in different regions besides the CNS. We previously reported the upregulation in ALS models of a gene called fibroblast-specific protein-1 or S100A4, recognized as a pro-inflammatory and profibrotic factor. Since inflammation and fibrosis are often mutual-sustaining events that contribute to establish a hostile environment for organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…WNT1 [182], NRGN (neurogranin) [183], CCK (cholecystokinin) [184], RGS4 [185], PLK2 [186], LINGO1 [187], UNC5D [188], MEF2D [189], CX3CL1 [190], PIN1 [191], RET (ret proto-oncogene) [192], NME1 [193], STX1B [194], CDK5 [195], NPTX2 [196], VAMP2 [197], PRKAR1B [198], CAP2 [150], SNCB (synuclein beta) [199], AP2M1 [200], S100A9 [201], TLR8 [202], SERPINA1 [203], CCR5 [204], NOD2 [205], TLR7 [202], HGF (hepatocyte growth factor) [206], TLR2 [207], PTPRC (protein tyrosine phosphatase receptor type C) [208], C3 [209], LAMP3 [210], GLI1 [211], GPR4 [212], TLR1 [213], OSMR (oncostatin M receptor) [214], NFATC2 [215], GPNMB (glycoprotein nmb) [216], NQO1 [217], B2M [218], TRDN (triadin) [219], HK2 [220], NEDD4 [221], ATP6 [222], COX2 [223], CASP6 [224], MYD88 [225], NFKBIA (NFKB inhibitor alpha) [226], IL13RA1 [227], ND1 [228], TP53INP1 [229], CSF1 [230], ITPKB (inositol-trisphosphate 3-kinase B) [231], ANXA1 [232], SUMO4 [233], ITGA8 [234] and REST (RE1 silencing transcription factor) [235] have been shown to be activated in PD . WNT1 [236], RTN4R [237], MEF2D [238], CX3CL1 [239], PIN1 [240], UNC13A [241], CDK5 [242], SLC30A3 [243], TUBA4A [244], BCL2A1 [245], CHI3L1 [246], SERPINA1 [247], CCR5 [248], C7 [249], S100A4 [250], C1QB [251], SPP1 [252], TLR7 [253], TLR2 [...…”
Section: Discussionmentioning
confidence: 99%
“…WNT1 [182], NRGN (neurogranin) [183], CCK (cholecystokinin) [184], RGS4 [185], PLK2 [186], LINGO1 [187], UNC5D [188], MEF2D [189], CX3CL1 [190], PIN1 [191], RET (ret proto-oncogene) [192], NME1 [193], STX1B [194], CDK5 [195], NPTX2 [196], VAMP2 [197], PRKAR1B [198], CAP2 [150], SNCB (synuclein beta) [199], AP2M1 [200], S100A9 [201], TLR8 [202], SERPINA1 [203], CCR5 [204], NOD2 [205], TLR7 [202], HGF (hepatocyte growth factor) [206], TLR2 [207], PTPRC (protein tyrosine phosphatase receptor type C) [208], C3 [209], LAMP3 [210], GLI1 [211], GPR4 [212], TLR1 [213], OSMR (oncostatin M receptor) [214], NFATC2 [215], GPNMB (glycoprotein nmb) [216], NQO1 [217], B2M [218], TRDN (triadin) [219], HK2 [220], NEDD4 [221], ATP6 [222], COX2 [223], CASP6 [224], MYD88 [225], NFKBIA (NFKB inhibitor alpha) [226], IL13RA1 [227], ND1 [228], TP53INP1 [229], CSF1 [230], ITPKB (inositol-trisphosphate 3-kinase B) [231], ANXA1 [232], SUMO4 [233], ITGA8 [234] and REST (RE1 silencing transcription factor) [235] have been shown to be activated in PD . WNT1 [236], RTN4R [237], MEF2D [238], CX3CL1 [239], PIN1 [240], UNC13A [241], CDK5 [242], SLC30A3 [243], TUBA4A [244], BCL2A1 [245], CHI3L1 [246], SERPINA1 [247], CCR5 [248], C7 [249], S100A4 [250], C1QB [251], SPP1 [252], TLR7 [253], TLR2 [...…”
Section: Discussionmentioning
confidence: 99%
“…This drug interferes with different markers of the disease, such as mTOR, STAT3, and NF-κB. Thus, it reduces inflammation and aggregates formation in skeletal muscle, and displays beneficial effects also on muscle atrophy, by promoting regeneration [99]. It has been found that mutations of SOD1 induce upregulation of c-Abl, an apoptosis-related gene, and a decrease of cell viability.…”
Section: Preclinical Studies and Proposed Drugs Able To Restore Skele...mentioning
confidence: 99%
“…We previously demonstrated that niclosamide inhibits microglia reactivity and migration; it reduces inflammation and fibrosis and promotes autophagy in familial and sporadic ALS fibroblasts [ 19 ]. Moreover, in a proof-of-concept experiment, niclosamide inhibited gliosis and fibrosis in the spinal cord and in the sciatic nerve, promoted regeneration, and reduced fibrosis and inflammation in the skeletal muscles of a small cohort of ALS mice [ 19 ].…”
Section: Introductionmentioning
confidence: 99%